THE USE OF ENGLISH-INDONESIAN CODE SWITCHING IN THE EFL CLASSROOMS: TEACHERS' MOTIVES AND STUDENTS' ATTITUDES - Rahmah, Azmia Naufala (2015)
Penelitian ini bertujuan untuk menginvestigasi motif-motif guru dan sikap siswa terhadap penggunaan alih kode bahasa di dalam kelas. Metode yang digunakan dalam penelitian ini adalah kombinasi antara kuantitatif dan kualitatif. Partisipan dalam penelitian ini adalah 3 guru Bahasa Inggris dan 62 siswa. Penelitian ini berdasarkan konsep Poplack (1980) untuk menemukan tipe-tipe alih kode bahasa dan Canagarajah (1995) untuk menemukan motif-motif guru. Berdasarkan hasil penelitian ditemukan bahwa (1) guru Bahasa Inggris memiliki 16 motif penggunaan alih kode bahasa di kelas, diantaranya menjelaskan konsep yang sulit, menjelaskan grammar secara eksplisit, mengecek pemahaman siswa, mengorganisir tugas-tugas di kelas, mengenalkan topik baru, membenarkan pengucapan kata dalam Bahasa Inggris, mempertahankan kedisiplinan di kelas, memberikan balikan kepada siswa, mendukung partisipasi siswa, membangun hubungan interpersonal antara guru dan siswa, mengurangi kegelisahan siswa dalam belajar Bahasa Inggris, meningkatkan motivasi dan kepercayaan diri siswa, memberikan contoh, bergurau dengan siswa, menegaskan sesuatu dan memperkuat pemahaman siswa; (2) Para siswa memiliki sikap positif terhadap penggunaan alih kode bahasa yang dilakukan oleh guru-guru mereka. ----------- This study aims to investigate the teachers' motives and the students' attitudes towards the use of code switching in the classrooms. This research employs mix method design between quantitative and qualitative study. The participants of this study are 3 English teachers and 62 students. The data analyzed based on Poplack (1980) to find out types of code switching and Canagarajah (1995) for finding the teachers' motives. It was found that (1) there are 16 teachers' motives of using code switching in the classrooms, explaining difficult concepts, explaining grammar explicitly, checking for comprehension, organizing classroom tasks, introducing unfamiliar materials/ topic, drawing students' attention to the correct pronunciation of sounds in English, maintaining classroom discipline and structure of the lesson, providing praise/feedback/personal remarks about students' performance, encouraging students' participation in classroom activities, building interpersonal relationships between the teacher and students, reducing students' anxiety in learning English, increasing students' motivation and confidence in learning English, giving example, joking with the students, confirming something, and strengthening students' comprehension; (2) the students have a positive attitude towards the use of code switching done by their teachers.